Historical perspectives: Development of the codes of ethics in the legal, medical and accounting professions - Backof, Jeanne F. (Journal of business ethics, 1991)
Members of the legal, medical and accounting professions are guided in their professional behavior by their respective codes of ethics. These codes of ethics are not static. They are ever evolving, responding to forces that are exogenous and endogenous to the professions. Specifically, changes in the ethical codes are often due to economic and social events, governmental influence, and growth and change within the professions. This paper presents an historical analysis of the major events leading to changes in the legal, medical and accounting codes of ethics.